The Relationship Of Online Learning With Interest In Learning Students During The Covid-19 Pandemic at SMK Singosari Deli Tua Year 2022 - Mona Fitri Gurusinga; Afrilius Simanjuntak (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Abstract Distance learning is an electronic-based learning process. This online learning system has no access restrictions, this allows learning to take more time. Interest in learning is one of the most important factors for the success of students' learning, interest arises from within the students themselves. Factors from outside the interest in learning are how the teacher teaches. The role of the teacher is very important to foster student interest in learning, one of which is by teaching in a fun way, providing constructive motivation. The aim of the research is to find out whether there is a relationship between online learning and student learning interest during the Covid-19 pandemic. This study uses quantitative research methods with a cross sectional survey approach. The sampling method is using probability sampling technique with random sampling with a total sample of 109 respondents. The research instrument used a questionnaire sheet. The results of the statistical test using the chi-square test with = 0.05 showed that there was a relationship between online learning and student interest in learning during the covid-19 pandemic with a value of sig. (2-tailed) thus Ho was rejected. This study shows that there is a relationship between online learning and student interest in learning during the COVID-19 pandemic at SMK SINGOSARI Deli Tua in 2022.